In vitro and in vivo Effects of Lactate on Metabolism and Cytokine Production of Human Primary PBMCs and Monocytes - Ratter, Jacqueline M.; Rooijackers, Hanne M. M.; Hooiveld, Guido J.; Hijmans, Anneke G. M.; de Galan, Bastiaan E.; Tack, Cees J.; Stienstra, Rinke (Frontiers in Immunology, 2018)
Lactate, the end product of anaerobic glycolysis, is produced in high amounts by innate immune cells during inflammatory activation. Although immunomodulating effects of lactate have been reported, evidence from human studies is scarce. Here we show that expression of genes involved in lactate metabolism and transport is modulated in human immune cells during infection and upon inflammatory activation with TLR ligands in vitro, emphasizing the importance of lactate metabolism in inflammation. Lactate induces metabolic reprogramming in innate immune cells, as evidenced by reduced glycolytic and increased oxidative rates of monocytes immediately after exposure to lactate. A short-term infusion of lactate in humans in vivo increased ex vivo glucose consumption of PBMCs, but effects on metabolic rates and cytokine production were limited. Interestingly, long-term treatment with lactate ex vivo, reflecting pathophysiological conditions in local microenvironments such as tumor or adipose tissue, significantly modulated cytokine production with predominantly anti-inflammatory effects. Inhibition of lactate metabolism in TLR4- versus TLR2-activated cells differentially affected cytokine production, further emphasizing the importance of lactate metabolism for immune cell function. Together, our findings reveal lactate as a modulator of immune cell metabolism which translates to reduced inflammation and may function as a negative feedback signal to prevent excessive inflammatory responses.